The Medieval Climate Anomaly in the Iberian Peninsula reconstructed from marine and lake records - Moreno, Ana; Pérez, Ana; Frigola, Jaime; Nieto-Moreno, Vanesa; Rodrigo-Gámiz, Marta; Martrat, Belén; González-Sampériz, Penélope; Morellón, Mario; Martín-Puertas, Celia; Corella, Juan Pablo; Belmonte, Ánchel; Sancho, Carlos; et al. (Quaternary Science Reviews, 2012)
Selected multi-proxy and accurately dated marine and terrestrial records covering the past 2000 years in the Iberian Peninsula (IP) facilitated a comprehensive regional paleoclimate reconstruction for the Medieval Climate Anomaly (MCA: 900–1300 AD). The sequences enabled an integrated approach to land–sea comparisons and, despite local differences and some minor chronological inconsistencies, presented clear evidence that the MCA was a dry period in the Mediterranean IP. It was a period characterized by decreased lake levels, more xerophytic and heliophytic vegetation, a low frequency of floods, major Saharan eolian fluxes, and less fluvial input to marine basins. In contrast, reconstruction based on sequences from the Atlantic Ocean side of the peninsula indicated increased humidity. The data highlight the unique characteristics of the MCA relative to earlier (the Dark Ages, DA: ca 500–900 years AD) and subsequent (the Little Ice Age, LIA: 1300–1850 years AD) colder periods. The reconstruction supports the hypothesis of Trouet et al. (2009), that a persistent positive mode of the North Atlantic Oscillation (NAO) dominated the MCA.
id: 2334